Revitalization of Internal Audit in The Framework of Developing a Risk Management Program as an Early Warning System: Case Study “Carrefour Indonesia” - IRSAN, Muhammad Syah (International Journal of Environmental, Sustainability, and Social Science, 2024)
This thesis discusses the revitalization of the main duties and functions of internal audit regarding the application of the Risk Management Program at "Carrefour Indonesia" in dealing with threats and/or risks that have an impact on the company's business continuity, both from internal and external sources such as regulations, competition, markets, mergers and acquisitions, resources, and others to provide early warning for companies in taking mitigation steps for all these threats and/or risks. This research was done in the form of a case study that aims to gain an in-depth understanding of Internal Audit, Risk Management, Early Warning Systems. The results of the research show that "Carrefour Indonesia" faces risks triggered by strategies that will be implemented in the future and the application of the Risk Management Program at "Carrefour Indonesia" has not optimally provided early warning for the company, so improvements are needed in the system, resources and structure. Company so that the Early Warning System can be integrated with Risk Management.